PF-26 The Use of Endemic Sulawesi Medaka Fish (Oryzias celebensis) as an animal model candidate - Dwi Kesuma Sari; Irma Andriani; Khusnul Yakin; Magfira Satya (Hemera Zoa, 2018)
Medaka fish (Oryzias sp) or also known as "rice fish" are non-consumption fish or ornamental fish that are in great demand by humans. Medaka fish is an animal model that is very well known and has been widely used by researchers in the world for studies in various fields of science, especially biology and medicine, as well as Zebras which have been developed as model animals. Medaka fish also used as animal models for testing Parkinson's disease caused by environmental pollution and genetic factors. Several types of mutant medaka fish have also been made for screening diabetes, cancer and other degenerative diseases.                    From the exploration results, the researchers showed that Sulawesi has a high endemism especially for the family Adrianichthyidae. The high endemism is not only supported by zoogeographic boundaries as islands located on the Weber line and Wellacea lines, but also because of this fish that are traded so that the chance of migrating this fish is small. These facts underlie the statements of several researchers that fish medaka can reveal the mystery of the evolution of aquatic fauna in Sulawesi.                    As an effort to develop Sulawesi Medaka fish (Oryzias celebensis) as a model animal, studies have been conducted with various histology studies with various staining methods in Sulawesi medaka fish so that Hasanuddin University is expected to be a gateway for researchers to obtain information about Medaka fish in the Sulawesi islands and as a center for learning fish medaka.